Site Setup Patirtan Watugede Singosari, Malang, Indonesia As a Spiritual Tourism Object - Rosalia Niniek Sri Lestari; Junianto Junianto; A. Tutut Subadyo (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Patirtan site is an ancient cultural relic, associated with the ritual bath with holy water. PatirtanWatugede site in Singosari Malang, is one of the ancient kingdom of Singhasari, which is a big kingdomin East Java. Spiritual tourism activities at temple sites and Patirtan sites in East Java and Malang Rayacontinue to increase. On the other hand, some Patirtan sites evolved into tourist destinations, undergoinguncontrolled development renovations. Utilization and development in the area of partial Patirtan sites,tend to contradict the concept of conservation. Through the historical approach, then analyzing thephysical character and function of Watugede's Patirtan site, as well as the value of society's preference,can be formulated the concept of Patirtan Area Arrangement as a tourist destination spiritual. There arefindings of the main elements used as a spiritual tourism activity on these Patirtan sites, namely: watersource, meditation area, ritual ceremonial courtyard and building site Patirtan. Formulation of ConceptThe arrangement and development of Patirtan website as a spiritual tourism object is done descriptively,with the implementation of Draft Drawing. The concept of Arrangement and development of Watugede'sPatirtan site as a spiritual tourism object was found as a result of research, by examining the phenomenonof Patirtan site in Malang Regency, which is related to the utilization, preservation of physical element,socio-culture, economy and environment.